3D Printed PLA Porous Scaffolds with Engineered Cell Size and Porosity Promote the Effectiveness of the Kelvin Model for Bone Tissue Engineering - Arman Barzgar Torghabeh; Iman Barzgar Torghabeh; Morteza Kafaee Razavi (Macromolecular Materials and Engineering)
Abstract In this study, the aim is to investigate the effect of engineering the cell size and porosity of 3D‐printed poly lactic acid (PLA) porous scaffolds from the Kelvin model for bone tissue engineering applications. The Kelvin model is used as a bone tissue scaffold with different cell sizes and porosities. PLA, as a biodegradable and biocompatible polymer, is used to fabricate these scaffolds using the FDM technique. A compression test is used to evaluate the mechanical properties of scaffolds. The MTT assay has been used to investigate cell viability. For osteogenic differentiation studies, ALP activity and ARS assays are used. Increasing the porosity reduces the mechanical properties of the scaffold. While increasing the cell size at constant porosity increases the Young's modulus and yield stress in the samples, it is also observed that, in high porosities, the increase in cell size weakens the mechanical properties. Also, Kelvin model scaffolds help the proliferation and osteogenic differentiation of cells and have no toxic effect. It is demonstrated that this approach promotes the effectiveness of the Kelvin architecture for bone tissue engineering. As a result, designing the most suitable model based on cell size and porosity for the treatment process in the targeted area could be promising.